Cellular Microenvironments: A Versatile Approach to Engineering Biomolecule‐Presenting Cellular Microenvironments (Adv. Healthcare Mater. 2/2013). Issue 2 (11th February 2013) - Lienemann, Philipp S.; Karlsson, Maria; Sala, Ana; Wischhusen, Hanna M.; Weber, Franz E.; Zimmermann, Roland; Weber, Wilfried; Lutolf, Matthias P.; Ehrbar, Martin
<x xml:space="preserve">Abstract</x> Biomimetic hydrogels are engineered to mimic extracellular microenvironments, as reported by Martin Ehrbar and co‐workers on page 292. The cover image shows schematically how these matrices can selectively capture proteins from solution and present them to target cells in close proximity, triggering a desired cellular response. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>